Engaruh Kinerja Lingkungan Dan Biaya Lingkungan Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2018 - Marini Asjuwita; Henri Agustin (Universitas Negeri Padang, 2020)
This study aims to analyze the effect of environmental performance on the level of profitability on manufacturing companies listed on the Stock Exchange in 2014-2018, analyze the effect of environmental costs on the level of profitability on manufacturing companies listed on the Stock Exchange in 2014-2018, and analyze the influence of environmental performance and costs environment has a joint influence on the level of profitability of manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018 ... The results of this sprove that (1) Environmental performance has no positive effect on prof tudy itability on manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. (2) Environmental costs do not have a positive effect on profitability on manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018.